Pendidikan Multikultural dalam Meningkatkan Karakter Keindonesiaan bagi Peserta Didik Sekolah Menengah Atas - Sabrina, Dio Yoan; Komariah, Siti; Wilodati, Wilodati (Jurnal Paedagogy, 2022)
This study aims to describe the knowledge and understanding of teachers of multicultural education in improving the Indonesian character of students at SMAN 3 Tualang. This study employed a case study research design and a qualitative approach. The study used a purposive sample strategy to choose the interviewees, divided into 13 key informants: teachers from SMAN 3 Tualang, two supporting informants, the Principal of SMAN 3 Tualang, and the Head of the Tualang Education Area. Data reduction, data display, andÂ conclusion drawing were all used in the data analysis process. By using data triangulation techniques, the accuracy of the data used in this study was further examined. According to research employing the social learning theory, teachers still do not understand and master with multicultural education, so its implementation is not optimal, resulting in the low Indonesian character of students at SMAN 3 Tualang.